Chronopharmacology - implications for diagnosis and treatment - Lemmer, Björn (Advances in noninvasive electrocardiographic monitoring techniques, 2000)
Circadian rhythms have been documented throughout the plant and animal kingdom at every level of eukariotic organization. Circadian rhythms are endogenous in nature, driven by oscillators or clocks (Aschoff 1963), and persist under free-running (e.g. constant darkness) conditions. The genes expressing the biological clock have been identified in various species (Drosophila melongaster, Neurospora, Mouse, Golden hamster). The endogenous clock in man does not exactly runs at a frequency of 24 hours but somewhat slower, environmental Zeitgebers (Aschoff 1965) such as the alternation of light and darkness entrain the circadian rhythm to a precise 24-hour period. The important feature of endogeneous biological rhythms is their anticipatory character. Thus, rhythmicity inherent to all living systems, allows them to adapt more easily and to better survive under changing environmental conditions during the 24 hours of a day as well as during varying conditions of the changing seasons.